Pengaruh Media Loose Parts untuk Perkembangan Kognitif Anak Usia 5-6 Tahun di PAUD RA Chairunnisa - Annafi' Nurul 'Ilmi Azizah; Astutik; Wahyu Widayanti; Ana Nisaul Arifah; Alfaein Nisa Nur Salamah; Rizky Amalia Muflihah (Universitas Islam Zainul Hasan Genggong, 2024)
Learning Outcomes in improving cognitive development of early childhood by using varied learning media made from natural materials and used materials around the school. The purpose of this study is to improve children's cognitive through loose parst media at PAUD RA CHAIRUNNISA. The research method used is descriptive qualitative method with the type of class action research. The research was conducted in class B aged 5-6 years PAUD RA CHAIRUNNISA in the village of Dukuh, Sukoharjo District, the research subjects amounted to 20 children. This research was conducted with a round of 2 cycles. Data collection techniques obtained through documentation and observation with four stages in each cycle, namely planning, implementation, observation and reflection. Data analysis used data reduction, data display and conclusion drawing. And the expected success indicator in this study is 75% in the category of developing very well. Based on the results of the study can show that the use of loose part media can improve children's cognitive abilities. The increase can be seen in the pre-research data from 20 children. After taking action in cycle I which developed very well there were 9 children (45%), in cycle II which developed very well there were 18 children (90%). This research was stopped until cycle II because it had met the predetermined success standards of developing very well.